Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Mengembangkan Pengetahuan dan Keterampilan Hidup Masyarakat sebagai Wujud Pengabdian di Desa Singajaya Kecamatan Cihampelas Kabupaten Bandung Barat: Pengabdian - Aulia Zahra Annabilah; Azka Akbar Febiandika; Fikfik Taufik; Ghaitsa Rahmania Putri; Hilmi Durroh Taqwiyah; Muchamad Fandu Surya Pringga; Reza Amalia; Rianti Afriliani; Rifa Salsabila Fauziah; Rizky Renanda Supriyadi; Vasya Lediana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Kuliah Kerja Nyata (KKN) is a tangible manifestation of the implementation of the Tri Dharma of Higher Education in the field of community service. The KKN program, which was carried out in Singajaya Village, Cihampelas District, West Bandung Regency, aims to develop community knowledge and life skills through a series of education, socialization, counseling, and training activities. The implementation method is carried out by field observation, greeting residents, education at school, nutrition counseling at posyandu, health socialization at village halls, and village administration digitization training. The results of the activity showed that there was an increase in students' understanding of bullying issues, time management, gadget use, and the dangers of promiscuity. Village communities also benefit from socialization of the use of BPJS, nutritional counseling, and the provision of additional food for toddlers. In addition, village officials acquire basic skills in digital-based administrative management. This KKN program proves that students play the role of facilitators as well as agents of change that can increase community capacity, strengthen independence, and encourage sustainable village development.